The relationship between 19‐year trends in medication use and changes in physical function among women in the mid‐life: A Study of Women's Health Across the Nation pharmacoepidemiology study. Issue 3 (21st September 2021) - Solomon, Daniel H.; Santacroce, Leah; Colvin, Alicia; Lian, Yinjuan; Ruppert, Kristine; Yoshida, Kazuki
Abstract: Purpose: Medication side effects are a major concern in aging adults who report using an increasing number of medications. The relationship between accumulating medication use and physical function has not been examined in a longitudinal cohort. Methods: We conducted a longitudinal cohort study using prospectively collected data from the Study of Women's Health Across the Nation (SWAN). Community‐dwelling women from five US cities were followed for up to 20 years. The exposure of interest was the number of prescription medications. They were examined as a count variable and then for specific categories of medication. The outcome of interest was physical function measured repeatedly using the short form (SF)‐36 physical function (PF) scale. Linear mixed models, using repeated measures of sociodemographics and comorbidities were assessed. Results: 1452 participants qualified for the analyses with a median follow‐up of 19.2 years. At baseline, the mean age was 46.5 years and 53.5% reported White race. Fully adjusted models demonstrated a reduction in the SF‐36 PF of 0.99 for each additional prescription medication used or a 6.14‐point reduction for women reporting more than five medications and an 8.92‐point reduction among those reporting more than 10 medications. These results were similar across race and ethnicity. Specific medication categories with a significant and largely negative impact (at least a two‐point reduction) on physical component score included beta‐blockers, analgesics, glucocorticoids, anticonvulsants, anxiolytics, anticoagulants, and anti‐depressants. Conclusions: There is a moderate association between increasing medication use and decreasing physical function among women transitioning through the mid‐life.